Role of synthesis time in shaping the morphology and structure of carbon nanowalls - Zhumadilov, B.Ye.; Zhumadilov, R.Ye.; Nemkayeva, R.R.; Markhabayeva, A.A.; Gabdullin, M.T.; Yerlanuly, Ye. (Recent Contributions to Physics, 2024)
Carbon nanowalls (CNWs), a unique class of vertically oriented graphene-based nanostructures, have attracted significant attention due to their promising applications in energy storage, electronics, and sensing technologies. These materials combine high surface area, excellent electrical conductivity, and tunable morphology, making them ideal for a range of functional devices. However, controlling their structural evolution during synthesis remains a critical challenge. This study aims to systematically investigate the effect of synthesis duration on the morphological, structural, and optical properties of CNWs grown on silicon substrates using capacitively coupled plasma-enhanced chemical vapor deposition (CCP-PECVD). The research focuses on understanding how variations in growth time influence nanowall formation, defect density, and surface characteristics, which are essential for tailoring material performance. The CNWs were synthesized at four different durations—30, 60, 90, and 120 minutes—and characterized using SEM, AFM, Raman spectroscopy, and UV–Vis reflectance analysis. The results demonstrate a clear time-dependent evolution in CNW morphology and structure: from sparse and disordered features at 30 minutes to dense, petal-like graphitic walls at 120 minutes. Raman analysis showed increasing defect density with time, followed by partial graphitization at longer durations. Optical measurements revealed reduced reflectance with increasing synthesis time, indicating enhanced light trapping and surface roughness.